Estudo dos efeitos anti-inflamatórios da nanopartícula de ouro em modelo de asma alérgica experimental - Santos, Rafael Vital dos (2014)
Treatment with gold nanoparticles (Au NPs) exhibit a variety of biological effects, including anti-inflammatory effects. In the present study, we investigated the effect of intranasal treatment with the Au NPs on allergic inflammatory response induced by ovalbumin (OVA) in rats subjected to experimental model of asthma. The animals were sensitized on days 0, 7 and 14 by intraperitoneal injection with 50 mg OVA. On days 21, 22 and 23 after the initial stimulus, the animals were challenged with OVA (50 mg / 25 μl PBS) intranasally. Treatment with the Au NPs (6 or 60 mg / kg) occurred 1 h before the antigen challenge, and the evaluation of the biological parameters performed 48 h after the last challenge. The effect of Au NPs in airway hyperresponsiveness induced by methacholine was investigated by determining the resistance and elastance; eosinophil infiltration, peribronchial fibrosis and mucus production were investigated using histological techniques; Leukocyte infiltration and production of pro-inflammatory mediators in allergic airways induced stimulation by enzyme- linked immunoassay (ELISA); The production of reactive oxygen species in vitro and in vivo measures was the reduction of nitroblue tetrazolium (NBT) and flow cytometry using cells labeled with 2 ', 7'-dichlorofluorescein diacetate (DCFH-DA), respectively; The interference ability of Au NPs on phagocytosis, generation of TNF-α in murine macrophages and viability was evaluated by determining the phagocytic capacity, ELISA and MTT method, respectively. In the lungs, treatment with Au NPs reduced eosinophil infiltration after OVA challenge by attenuated production of mucus reversed resistance and increased lung compliance and decreased levels of IL-4, IL-13, KC, eotaxin-1 and eotaxin-2 in the lung tissue. Additionally, in vitro, macrophages exposed Au NPs in non-cytotoxic doses, when activated with zymosan showed a decrease in the production of reactive oxygen species (ROS) and secretion of TNF-α. Taken together, our results demonstrate the anti-inflammatory properties of the Au NPs and its association with reduced leukocyte infiltration, suppression of production of proinflammatory cytokines and antioxidant effect. The Au NPs were found to be a therapeutic option for the treatment of allergic inflammation.